Effects of menstrual cycle phase on metabolomic profiles in premenopausal women - Wallace, M.; Hashim, Yumi Zuhanis Has-Yun; Wingfield, M.; Culliton, M.; McAuliffe, F.; Gibney, M. J.; Brennan, L. (Oxford University Press /The European Society of Human Reproduction and Embryology, 2010)
Background: Characterization of the normal degree of physiological variation in the metabolomic profiles of healthy humans is a necessary step in the development of metabolomics as both a clinical research and diagnostic tool. This study investigated the effects of the menstrual cycle on 1H nuclear magnetic resonance (NMR) derived metabolomic profiles of urine and plasma from healthy women.